The central unit within the 19S regulatory particle of the proteasome - Rosenzweig, Rina (2008)
The 26S proteasome is a multisubunit enzyme composed of a cylindrical catalytic core (20S) and a regulatory particle (19S) that together perform the essential degradation of cellular proteins tagged by ubiquitin. To date, however, substrate trajectory within the complex remains elusive. Here we describe a previously unknown functional unit within the 19S, comprising two subunits, Rpn1 and Rpn2. These toroids physically link the site of substrate recruitment with the site of proteolysis. Rpn2 interfaces with the 20S, whereas Rpn1 sits atop Rpn2, serving as a docking site for a substrate-recruitment factor. The 19S ATPases encircle the Rpn1-Rpn2 stack, covering the remainder of the 20S surface. Both Rpn1-Rpn2 and the ATPases are required for substrate translocation and gating of the proteolytic channel. Similar pairing of units is found in unfoldases and nuclear transporters, exposing common features of these protein nanomachines.